2019
DOI: 10.1016/j.energy.2019.05.012
|View full text |Cite
|
Sign up to set email alerts
|

Experimental study and numerical modelling of high temperature gas/solid packed-bed heat storage systems

Abstract: Two pilot-scale regenerative heat storage systems have been tested by the French Alternative Energies and Atomic Energy Commission (CEA). The first one is a 1.1-MWhth structured packed bed consisting of ceramic plates forming corrugated channels. The second one is a 1.4-MWhth granular packed bed consisting of basaltic rocks enclosed by refractory walls. The two regenerators were tested over a hundred of thermal cycles between 80°C and 800°C with different fluid mass flows. Both systems showed their ability to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(5 citation statements)
references
References 40 publications
1
4
0
Order By: Relevance
“…Globally, numerical results fitted well experimental points which indicates that the TES performances were consistent to the design. During the first hours of charging, the thermocline entirely occupied the tank, similarly to the observation of Esence et al [13]. At the end of the charge, the temperature was constant at 525°C (feeding temperature) in the first meter length of the tank.…”
Section: Temperature Evolutionsupporting
confidence: 74%
See 3 more Smart Citations
“…Globally, numerical results fitted well experimental points which indicates that the TES performances were consistent to the design. During the first hours of charging, the thermocline entirely occupied the tank, similarly to the observation of Esence et al [13]. At the end of the charge, the temperature was constant at 525°C (feeding temperature) in the first meter length of the tank.…”
Section: Temperature Evolutionsupporting
confidence: 74%
“…Esence et al observed a thermal discrepancy of 250°C in the corner of the tank, indicating high velocities due to the channeling effects [13]. This phenomenon is absent in this study, since the thermocouples temperature is relatively homogeneous, meaning an equal distribution of the fluid velocity along the cross section.…”
Section: Temperature Evolutionmentioning
confidence: 50%
See 2 more Smart Citations
“…Doppiu et al [2] put forward an alternative material for thermal storage, analyzed different components theoretically, and measured the reversibility and stability of the material under experimental conditions. Esence et al [3] compared the thermal performance between two regenerators, and evaluated their operating errors. Tian et al [4] simulated the effective thermal conductivity of an autoclave aerated concrete (AAC).…”
Section: Introductionmentioning
confidence: 99%